1996
DOI: 10.2527/1996.741151x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of immune response in lambs during treatment with the beta-adrenergic agonist clenbuterol.

Abstract: The effect of the beta-adrenergic agonist clenbuterol on immune function was examined in sheep. Twenty ewe lambs were housed indoors, with food and water available on an ad libitum basis, and immunized against somatostatin (SRIF) using a SRIF-ovalbumin conjugate. Ten of the lambs were also treated with clenbuterol (400 micrograms/kg) each day; 10 controls were not treated. After 5 wk of treatment (with booster injections of the SRIF conjugate each fortnight), the lambs were bled and then slaughtered for carcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…This is consistent with previous studies that reported that betaagonists do not affect cortisol concentration in lambs and calves under conventional conditions (Beermann et al 1987;Chikhou et al 1991;Sauerwein et al 1993). Although it was reported that clenbuterol suppressed humoral immunological function in lambs (Spencer and Oliver 1996), our results indicate that L-644,969 did not affect cellmediated immune response in terms of leukocyte profile and lymphocyte function. Acute stress, but not chronic treatment with salbutamol (a beta-agonist), resulted in an increase in cortisol concentration (Jensen et al 1994).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with previous studies that reported that betaagonists do not affect cortisol concentration in lambs and calves under conventional conditions (Beermann et al 1987;Chikhou et al 1991;Sauerwein et al 1993). Although it was reported that clenbuterol suppressed humoral immunological function in lambs (Spencer and Oliver 1996), our results indicate that L-644,969 did not affect cellmediated immune response in terms of leukocyte profile and lymphocyte function. Acute stress, but not chronic treatment with salbutamol (a beta-agonist), resulted in an increase in cortisol concentration (Jensen et al 1994).…”
Section: Discussionsupporting
confidence: 82%
“…There is evidence that animals treated with beta-agonists appear to be more nervous in a new environment and responsive to stressful situations, as indicated by higher plasma concentration of adrenocorticotropic hormone (ACTH) and cortisol (Bruckmaier and Blum 1992;Jensen et al 1994). Spencer and Oliver (1996) reported that a beta-agonist, clenbuterol, reduced antibody titer by 10 times in lambs, suggesting that beta-agonist treatment of animals may inhibit humoral antibody response to infection. However, with long-term of administration of a beta-agonist, salbutamol, to lambs, Bassett et al (1993) did not find any change in response to dipping stress.…”
mentioning
confidence: 99%
“…However, whereas clenbuterol relieves the symptoms of respiratory disease, it does not improve the horse's resistance to pulmonary infectious agents such as viruses and bacteria (Kastner et al, 1999). In fact, data from sheep demonstrate that β-adrenergic agonists, such as clenbuterol, may alter immune function in vitro (Spencer and Oliver, 1996). Data on the secondary humoral immune antibody response in vivo suggest that clenbuterol has a suppressive effect on humoral antibody response to infection (Spencer and Oliver, 1996).…”
Section: Bcmentioning
confidence: 99%
“…In fact, data from sheep demonstrate that β-adrenergic agonists, such as clenbuterol, may alter immune function in vitro (Spencer and Oliver, 1996). Data on the secondary humoral immune antibody response in vivo suggest that clenbuterol has a suppressive effect on humoral antibody response to infection (Spencer and Oliver, 1996). Those studies focused on chronic administration of clenbuterol.…”
Section: Bcmentioning
confidence: 99%
See 1 more Smart Citation